Perspectives of Snake Owners in Indonesia on Understanding Information about Snakes and Snakebites - Rayhani, Fahira Salima; Agustin, Herlina; Gumilar, Gumgum (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
This study uses a mixed-methods approach to examine the perspectives of snake owners in Indonesia regarding snakes, venomous species, and snakebite management. A survey was distributed to 1,109 respondents, with 109 participants) forming the core group for analysis. The research aims to assess snake owners’ knowledge about venomous snakes, handling snakebites, and myths surrounding these reptiles. Findings indicate that while the public generally fears snakes, many reptile enthusiasts in Indonesia keep snakes as pets for reasons such as hobby, conservation, and education. However, a significant gap in knowledge exists regarding the identification of venomous versus non-venomous snakes, with some respondents unable to distinguish between them accurately. Additionally, while most respondents recognized the importance of immobilization following a snake bite, some still believed in outdated and dangerous practices, such as suctioning or cutting the wound. The study also uncovered that while most participants view snakes as ordinary creatures, a small portion still holds superstitions, such as believing snakes are evil spirits. This perpetuates fear and misunderstanding of snakes. In conclusion, the research highlights the need for better education on snake identification, proper bite management, and debunking myths to improve the safety of snake keeping in Indonesia. Increased public awareness and accurate information can help mitigate the risks of keeping snakes as pets and foster a more informed and responsible approach to reptile care.